Pre-frailty is associated with higher risk of gastroesophageal reflux disease: a large prospective cohort study - Lei Peng; Xueqin Li; Jinfeng Qi; Yangang Shan; Liming Zhang; Zhenqing Yang; Xucheng Wu; George O. Agogo; Zuyun Liu; Genxiang Mao; Honglei Wu (Scientific Reports)
Abstract To investigate the prospective association of frailty status, especially the early stage, with the long-term risk of Gastroesophageal reflux disease (GERD) in a large prospective cohort. We included participants who were free of GERD and cancer at baseline and use of aspirin and non-steroidal anti-inflammatory drugs (NSAIDs) from the UK Biobank (UKB). Frailty status was assessed using Fried phenotype including five items (weight loss, exhaustion, low grip strength, low physical activity, slow walking pace) and classified as non-frail, pre-frail, and frail. The outcome was incident GERD. The frailty status was assessed using Cox proportional hazard model. Among 327,965 participants (mean age 56.6 years) at baseline, 151,689 (46.3%) were pre-frail and 14,288 (4.4%) were frail. During a median of 13.5-years of follow-up, 31,027 (9.5%) participants developed GERD. Compared with non-frail participants, pre-frail (hazard ratios [HR] = 1.21, 95% confidence interval [CI] 1.18–1.24) and frail (HR = 1.60, 95% CI 1.52–1.68) participants had significantly higher risks of GERD. Among the five indicators of frailty, exhaustion demonstrated the strongest association with the risk of GERD (HR = 1.42, 95% CI 1.38–1.47). Subgroup analysis showed strong associations among younger (< 60 years), female, high-educated, unemployed participants, and those who had BMI < 18.5 kg/m2 (all P for interaction < 0.05). Frailty, especially pre-frail, which is potentially reversible, was associated with higher risk of GERD in middle-aged and older individuals. The findings underscore the importance of integrating routine frailty assessments and interventions, especially at the early stage, to improve digestive health.